EhRho6‐mediated actin degradation in Entamoeba histolytica is associated with compromised pathogenicity. Issue 5 (6th April 2022) - Narooka, Anil Raj; Apte, Achala; Yadav, Pooja; Murillo, Jimmy Rodriguez; Goto‐Silva, Livia; Junqueira, Magno; Datta, Sunando
Abstract: Entamoeba histolytica causes amoebiasis which is a major health concern in developing countries. E. histolytica pathogenicity has been implicated to a large repertoire of small GTPases which switch between the inactive GDP bound state and the active GTP bound state with the help of g uanine nucleotide e xchange f actors (GEFs) and G TPase a ctivating p rotein (GAPs). Rho family of small GTPases are well known to modulate the actin cytoskeletal dynamics which plays a major role in E. histolytica pathogenicity. Here, we report an atypical amoebic RhoGEF, and its preferred substrate EhRho6, which, upon overexpression abrogated the pathogenic behavior of the amoeba such as adhesion to host cell, monolayer destruction, erythrophagocytosis, and formation of actin dots. A causative immunoblot analysis revealed actin degradation in the EhRho6 overexpressing trophozoites that could be inhibited by blocking the amoebic proteasomal pathway. A careful analysis of the results from a previously published transcriptomics study, in conjunction with our observations, led to the identification of a clade of Rho GTPases in this pathogenic amoeba which we hypothesize to have implications during the amoebic encystation. Abstract : The transmission of Entamoeba histolytica from one host to another depends on its ability to undergo encystation. In this study, we identified a novel EhRhoGEFduo and its substrate RhoGTPases which are involved in the actin degradation and we hypothesize its implications in amoebic encystation. This study is the first report of Rho family members associated with the degradation of actin in E. histolytica .